Agostinho da Silva: a poetic construction of existence = Agostinho da Silva: uma poética construção da existência - Pereira, Paula Cristina (2008)
Believing that the construction of existence is poetic and religious so that life fulfils itself and that the Portuguese way of thinking, more conceptional than conceptual, finds in the Thinker of the World to Be one of its clearest and deepest expressions, the reflexion suggested in this paper arises from the intimate relationship between poetry and love, highlighting the brotherly unity of the aesthetical, antropological, ethical and political dimensions when one thinks and lives a project of hope -for man and his common home- spun by the Kingdom of Spirit.